Piezoelectric Based Vibration Energy Harvester - Mohammad, Mohd Yusof (Universiti Sains Malaysia, 2017)
In this project, some of the shortcomings in the existing system have been proposed to be rectified. The advances in technology have allowed numerous ways for power harvesting systems in practical applications in order to meet the power demand. The use of piezoelectric crystal is to generate electric output from surrounding vibrations. Piezoelectric materials have a crystalline structure that can convert mechanical energy into electrical charge and vice-versa. Harvesting mechanical energy from human motion is an attractive approach for obtaining clean and sustainable electric energy to power wearable sensors, which are widely used for health monitoring, activity recognition, gait analysis and so on. This project studies a piezoelectric energy harvester for the parasitic mechanical energy in shoes originated from human motion. The harvester is based on a specially designed sandwich structure with a thin thickness, which makes it readily compatible with a shoe. Besides, consideration is given to both high performance and excellent durability. The different values of frequencies will be taken to indicate the shoe while walking, jogging and running. In order to increase the voltage, the boost converter circuit is used. The use of boost converter is to increase the level of voltage ranges and the charge then will be stored in a supercapacitor. Time duration for the supercapacitor to fully charged will be taken.